Aplicación de las normas internacionales de información financiera (Niif) para pymes servicios en telefonía en la empresa “Valdivieso line” de la ciudad de Latacunga provincia de Cotopaxi en el período 01 de enero al 31 de diciembre del 2012 - Salazar Curco, Abrahan Isaías (2015)
The thesis is developed in order to apply the International Financial Reporting Standards (NIIF) for Small and Medium Enterprises (PYMES) in Valdiviezo Line company that is dedicated to the marketing of mobile phones, also authorized dealer in Movistar customer attention and prepay card selling, the main objective was to have relevant and real information of the financial position and the performance of the company to follow for the first-time adoption of NIIF in PYMES. So we think the guidelines required by the new regulations, we took into account the sections of NIIF for PYMES involved in the change process, the information based on concepts that helped us understand the basic terms of the topic explained the issue as detailed by the theoretical framework and fundamental research categories was found that there is still a lack of these regulations.